2009
DOI: 10.1111/j.0105-2896.2009.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

IRF4 and its regulators: evolving insights into the pathogenesis of inflammatory arthritis?

Abstract: SummaryAccumulating evidence from murine and human studies supports a key role for interleukin-17 (IL-17) and IL-21 in the pathogenesis of inflammatory arthritis. The pathways and molecular mechanisms that underlie the production of IL-17 and IL-21 are being rapidly elucidated. This review focuses on interferon regulatory factor 4 (IRF4), a member of the IRF family of transcription factors, which has emerged as a crucial controller of both IL-17 and IL-21 production. We first outline the complex role of IRF4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 178 publications
(328 reference statements)
5
77
0
Order By: Relevance
“…IRF4 is known to interact with a number of other transcription factors, including ETS factors and AP1 family members. In different settings, these interactions are critical in determining the DNA-binding specificity and functional nature of the IAD, either as an activator or repressor of transcription [91][92][93]. However, whether these interactions occur within the context of DCs remain to be defined, although PU.1 (ETS) and Batf3 (AP1) are attractive candidates.…”
Section: Factors Regulating Late DC Progenitor Developmentmentioning
confidence: 99%
“…IRF4 is known to interact with a number of other transcription factors, including ETS factors and AP1 family members. In different settings, these interactions are critical in determining the DNA-binding specificity and functional nature of the IAD, either as an activator or repressor of transcription [91][92][93]. However, whether these interactions occur within the context of DCs remain to be defined, although PU.1 (ETS) and Batf3 (AP1) are attractive candidates.…”
Section: Factors Regulating Late DC Progenitor Developmentmentioning
confidence: 99%
“…The Rho kinase family members, consisting of Rho-associated kinase 1 (ROCK1) and ROCK2, are serine-threonine kinases that are activated by Rho GTPases and mediate the phosphorylation of downstream targets in cells (9). Recent studies have demonstrated that ROCK2 regulates the production of both IL-21 and IL-17 and plays an essential role in the development of autoimmunity in mice (10,11). Indeed, pan ROCK inhibition was reported to effectively down-regulate ongoing autoimmune response in animal models (11,12).…”
mentioning
confidence: 99%
“…Consistent with these data, our adoptive transfer study showed that IRF4 deficiency in effector T cells conferred disease resistance in recipient mice in a gene-dose-dependent manner. These results suggest that the dosage of IRF4 affects the function of autoreactive Cell number, ×10 6 …”
Section: Discussionmentioning
confidence: 90%
“…A series of reports have documented that IRF4 plays pleiotropic roles in lymphoid development and its immune response [6,7]. At the molecular level, studies have suggested that IRF4, together with BATF (basic leucine zipper transcription factor ATF-like) and the activator protein-1 family member JUN, acts as a 'pioneer transcriptional factor' that prepares chromatin accessibility for the subsequent lineage-specific transcriptional factor and drives gene expression for the differentiation of effector T cells [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation